eCM 2010
DOI: 10.22203/ecm.v020a05
|View full text |Cite
|
Sign up to set email alerts
|

Short bouts of mechanical loading are as effective as dexamethasone at inducing matrix production by human bone marrow mesenchymal stem cells

Abstract: Dexamethasone (Dex) is used widely to induce differentiation in human mesenchymal stem cells (hMSCs); however, using a pharmaceutical agent to stimulate hMSC differentiation is not the best choice for engineered tissue transplantation due to potential side-effects. The goal of the present study was to investigate the effects of dynamic compressive loading on differentiation and mineralized matrix production of hMSCs in 3D polyurethane scaffolds, using a loading regimen previously shown to stimulate mineralised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 70 publications
(55 reference statements)
6
64
1
Order By: Relevance
“…However, our model predicts that under a compressive strain of 5% (1Hz) in 400μm pore-size scaffolds, which has been experimentally shown to achieve enhanced osteogenic differentiation (i.e. higher ALP, osteopontin expression and calcium content) of human bone marrow-derived MSCs (Sittichokechaiwut et al 2010), the resulting WSS would be between 4.12-7.18mPa and thus well within the range to stimulate an osteogenic response. In addition, an in vivo study by Duty et al (2007), it was found that bone tissue formation and mineralisation were enhanced within a porous PLA scaffold (p=71%, d=397µm) under dynamic compression with a compressive strain of 1.8% and frequency of 1Hz.…”
Section: Discussionmentioning
confidence: 91%
“…However, our model predicts that under a compressive strain of 5% (1Hz) in 400μm pore-size scaffolds, which has been experimentally shown to achieve enhanced osteogenic differentiation (i.e. higher ALP, osteopontin expression and calcium content) of human bone marrow-derived MSCs (Sittichokechaiwut et al 2010), the resulting WSS would be between 4.12-7.18mPa and thus well within the range to stimulate an osteogenic response. In addition, an in vivo study by Duty et al (2007), it was found that bone tissue formation and mineralisation were enhanced within a porous PLA scaffold (p=71%, d=397µm) under dynamic compression with a compressive strain of 1.8% and frequency of 1Hz.…”
Section: Discussionmentioning
confidence: 91%
“…5% global strain of compression was applied for bone formation (Sittichockechaiwut et al 2009;Sittichokechaiwut et al 2010). Although, it was proved mechanical stimulation affected the cell behavior in the construct as a whole, few researches looked into a scaffold to find the differences among areas except for some computer models (Lacroix et al 2006;O'Brien et al 2007).…”
Section: Bioreactor Design and Loading Applicationmentioning
confidence: 99%
“…A bioreactor provides a controllable environment to create a bio-tissue both for systematic scientific research and for potential using in implant and replacement of damaged tissue (Sittichockechaiwut et al 2009;Sittichokechaiwut et al 2010).With regarding to mimicking the dynamics of the in vivo environment, the complexity of mechanical properties in different tissues (e.g. bone, cartilage, tendon and ligament, and cardiovascular tissue) should be considered and distinguished (Huselstein et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Commonly a gel based scaffold or tissue culture plastic has been used as the substrate on which cells were mechanically loaded, and the strain employed has been in the range of 2%-20%. 6,[12][13][14][15][16][17][18][19][20] Neither the scaffold nor the strain of this magnitude represents the true environment or magnitude of physiological or pathological loading of bone in humans in vivo. Further, a number of studies in vivo have been carried out in an attempt to overcome these obstacles, but these are limited to animal models and therefore could be associated with differences in responses to loading and mechanisms involved from one species to another.…”
mentioning
confidence: 99%